The Influence of Academic Service Quality on Students’ Satisfaction for Pertiwi University Students - Suryati, Suryati; Dina, Nur; Irawan, Pristanto Ria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The quality of academic services covers various aspects, starting from the quality of teaching, learning facilities, administration systems, to counseling and career guidance services. Each of these components plays a role in shaping students' perceptions of their educational experience at university. The author is interested in taking the variables of academic service quality and students’ satisfaction at Pertiwi University for research. The aim of this research is to determine the influence of service quality regularly partial towards students’ satisfaction with Pertiwi University students. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. In this research, a purposive sampling method was used, totaling 73 students at Pertiwi University with a simple linear regression data analysis technique. The results of this research show that there is an influence on the quality of academic services regularly, with a partial impact on students’ satisfaction at Pertiwi University. The results of this research are expected to contribute to further research.